Environmental interactions of tidal lagoons: A comparison of industry perspectives. (April 2018) - Elliott, Kathryn; Smith, Helen C.M.; Moore, Francesca; van der Weijde, Adriaan H.; Lazakis, Iraklis
Abstract: Tidal lagoons are an attractive renewable energy option that could aid the UK in meeting its ambitious renewable energy targets. One of the main barriers to tidal range development in the UK to date has been regulatory environmental concern. In order for the nascent lagoon industry to move forward into development, the views of the developers and other influential stakeholders such as government bodies, regulators, conservationists and practitioners (herein referred to as 'influencing stakeholders' or 'influencers') need to be aligned. This study is the first of its kind using online questionnaires and semi-structured interviews to present and compare the views of both developers and influencing stakeholders on the environmental interactions of tidal lagoons. We find that, whilst both influencers and developers are working towards the common goal of a good environmental outcome for tidal lagoons, there are mismatches in their views in terms of the priorities given to the key environmental impacts, benefits and potential solution options. The work provides insight into what is at the forefront of developers' and influencers' minds, highlighting the key themes within their views and transforming this information into policy recommendations that will help the industry's development move forward. Highlights: The lagoon industry is collectively working towards a good environmental outcome. Mismatches in views arise in the detail of impacts, benefits and solution options. Understanding behind the differing developer and influencer views is presented. It is recommended that lagoon-specific regulatory policy is introduced.